[Collection of documents regarding Hispanic Coalition activities involving cigarette taxes] - PAUL JOHNSON (Tufts Archival Research Center, 2007)
Illegible/Difficult to Read; Missing Attachments; Marginalia; Collection of documents collected by Fleishman Hillard regarding Hispanic Coalition activities involving cigarette taxes. Includes copies of thank you letters to Congressmen and letters to the editor. Categorizes Hispanic groups in terms of groups with an established relationship with the Tobacco Institute (TI), and groups they would like to be involved with. Discusses distribution of a Hispanic anti tax brochure.